L’activité prébiotique des mucilages et des pectines extraits des grains de fenouil : Applications alimentaires dans les formulations de yaourts fonctionnels. - MEKKI Rachida (My University, 2025)
The objective of this study was to evaluate the effect of adding mucilages and pectins extracted from Foeniculum vulgare seeds as natural additives on the physicochemical quality, stability, and microbiological characteristics of a functional yogurt enriched with probiotics. The yogurts were prepared from cow’s milk following a standard fermentation process and divided into several experimental batches supplemented with increasing levels of fennelextracts. Physicochemical and microbiological analyses were carried out during storage at 4°C for 15 days. The results revealed that the incorporation of fennel mucilages and pectins stimulated the growth and viability of probiotic bacteria while maintaining a stable pH ranging from 4.4 to 4.6 and a progressive increase in acidity reaching about 97 °D, indicating a controlled fermentation and good product stability. The addition of these extracts also improved yogurt texture and viscosity, ensuring better consistency during storage. Microbiologically, the fennel extracts inhibited the proliferation of undesirable microorganisms while promoting the growth of beneficial lactic acid bacteria, confirming their role as natural prebiotics. These findings highlight the potential of fennel-derived mucilages and pectins to enhance the quality, stability, and functional value of probiotic- enriched yogurts, providing a promising base for the development of healthy and innovative dairy products.
Keywords: Foeniculum vulgare; mucilages; pectins; functional yogurt; probiotics; microbiology; quality; preservation.